Spectroscopic evidences for the size dependent generation of pd species responsible for the low temperature CO oxidation activity on Pd-SBA-15 nanocatalyst - Soni, Yogita; Pradhan, Sumanta; Bamnia, Mahesh K.; Yadav, A. K.; Jha, S. N.; Bhattacharyya, D.; Khan, Tuhin Suvra; Haider, M. A.; Vinod, C. P. (Applied Catalysis B-Environmental, 2020)
A comprehensive size dependent CO oxidation activity has been demonstrated for Pd-SBA-15 catalysts with Pd NPs of varying sizes such as 1-2, 4-6 and 7-10 nm. Pd-SBA-15 catalyst with smallest sized NPs (Pd-S-N) has been synthesized by modified deposition precipitation method recently developed in our lab. Pd-S-N catalyst (reduced at 400 degrees C) demonstrated CO oxidation activity with lower light off temperature (50 degrees C), clearly one of the best reported for a Pd-silica system. A detailed XPS and in-situ DRIFTS analyses further supported by XAS and DFT calculations reveal the presence of easily decomposable highvalent Pd-oxide on co-ordinatively unsaturated Pd sites (Pdcus). Weak binding of CO on Pdcus sites in small Pd NPs leaving sites for oxygen activation is attributed to the low temperature activity of Pd-S-N for CO oxidation.
Keywords: CO oxidation; high-valent Pd species; Pd nanoparticles; SBA-15; under coordinated Pd atoms

Direct oxidation of cyclohexane to adipic acid by a WFeCoO(OH) catalyst: role of bronsted acidity and oxygen vacancies - Vernekar, Dnyanesh; Dayyan, Mohammad; Ratha, Satyajit; Rode, V, Chandrashekhar; Haider, M. Ali; Khan, Tuhin Suvra; Jagadeesan, Dinesh (ACS Catalysis, 2021)
This work reports the catalytic activity of the trimetallic mixed-metal oxyhydroxide WFeCoO(OH) for the direct oxidation of cyclohexane to adipic acid (AA) without the use of concentrated HNO3. WFeCoO(OH) displayed a 40% conversion of cyclohexane and a 67% selectivity to AA under relatively milder conditions of temperature (90 degrees C) and pressure (1 atm). Experimental evidence confirmed the presence of acidic, basic, and redox sites on WFeCoO(OH). The detailed investigation revealed that doping W in the Co-FeO(OH) matrix increased the amount of surface lattice oxygen (OS-L) and caused a significant surge in acidity (5.1 mmol/g). The calculated deprotonation energy of WFeCoO(OH) was 1434 kJ/mol, and the trend in acidity was WCoO(OH) < WFeCoO(OH) < FeCoO(OH) similar to CoO(OH). Energy calculations showed that WFeCoO(OH) had a high propensity to generate oxygen vacancies by the loss of either a water molecule or an oxygen atom (-132.2 or -140.9 kJ/mol, respectively). Basicity was generated due to the presence of conjugate pairs of the surface hydroxyl groups. The combined action of the trifunctional acidic, basic, and redox-active metal centers along with the oxygen vacancies was responsible for the enhanced catalytic performance.
Keywords: Adipic Acid; deprotonation energy; metal oxyhydroxides; multifunctional catalysts; oxygen vacancies

In-situ experimental and computational approach to investigate the nature of active site in low-temperature CO-PROX over CuOx-CeO2 catalyst - Adak, Shubhadeep; Rabeah, Jabor; Ranjan, Ravi; Khan, Tuhin Suvra; Poddar, Mukesh Kumar; Gupta, Rishi Kumar; Sasaki, Takehiko; Kumar, Sagar; Bordoloi, Ankur; Gopinath, Chinnakonda S.; Bruckner, Angelika; Bal, Rajaram (Applied Catalysis A-General, 2021)
Preferential oxidation (PROX) of carbon monoxide (CO) in presence of excess hydrogen is a necessity to prevent poisoning of the Pt-anode by CO in PEMFCs (Polymer Electrolyte Membrane Fuel Cell). A highly active catalyst, 5 wt% Cu-CeO2 showed 100 % CO conversion at 65 degrees C without any undesirable oxidation of H-2. The catalyst showed no deactivation even after 100 h on stream, making it viable for practical fuel cell application. Operando EPR in the PROX reaction condition revealed highly dispersed mixed valent cations with oxygen vacancies, responsible for the low-temperature PROX activity. At the active site, both Cu and Ce ions were shown to reversibly change their valence states to facilitate the abstraction of bridging lattice oxygen for CO oxidation to CO2. This surface oxygen mediated CO oxidation was found to be much faster than that of H-2 to H2O, which could explain the complete selectivity of oxygen for CO2 formation.
Keywords: CuOx-CeO2; interface; Oxygen vacancy; PROX; Synergistic

Unravelling faradaic electrochemical efficiencies over Fe/Co spinel metal oxides using surface spectroscopy and microscopy techniques - Kashyap, Varchaswal; Pandikassala, Ajmal; Singla, Gourav; Khan, Tuhin Suvra; Haider, M. Ali; Vinod, C. P.; Kurungot, Sreekumar (Nanoscale, 2022)
Cobalt and iron metal-based oxide catalysts play a significant role in energy devices. To unravel some interesting parameters, we have synthesized metal oxides of cobalt and iron (i.e. Fe2O3, Co3O4, Co2FeO4 and CoFe2O4), and measured the effect of the valence band structure, morphology, size and defects in the nanoparticles towards the electrocatalytic hydrogen evolution reaction (HER), the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR). The compositional variations in the cobalt and iron precursors significantly alter the particle size from 60 to <10 nm and simultaneously the shape of the particles (cubic and spherical). The Tauc plot obtained from the solution phase ultraviolet (UV) spectra of the nanoparticles showed band gaps of 2.2, 2.3, 2.5 and 2.8 eV for Fe2O3, Co3O4, Co2FeO4 and CoFe2O4, respectively. Further, the valence band structure and work function analysis using ultraviolet photoelectron spectroscopy (UPS) and core level X-ray photoelectron spectroscopy (XPS) analyses provided better structural insight into metal oxide catalysts. In the Co3O4 system, the valence band structure favors the HER and Fe2O3 favors the OER. The composites Co2FeO4 and CoFe2O4 show a significant change in their core level (O 1s, Co 2p and Fe 2p spectra) and valence band structure. Co3O4 shows an overpotential of 370 mV against 416 mV for Fe2O3 at a current density of 2 mA cm(-2) for the HER. Similarly, Fe2O3 shows an overpotential of 410 mV against the 435 mV for Co3O4 at a current density of 10 mA cm(-2) for the OER. However, for the ORR, Co3O4 shows 70 mV improvement in the half-wave potential against Fe2O3. The composites (Co2FeO4 and CoFe2O4) display better performance compared to their respective parent oxide systems (i.e., Co3O4 and Fe2O3, respectively) in terms of the ORR half-wave potential, which can be attributed to the presence of the oxygen vacancies over the surface in these systems. This was further corroborated in density functional theory (DFT) simulations, wherein the oxygen vacancy formation on the surface of CoFe2O4(001) was calculated to be significantly lower (similar to 50 kJ mol(-1)) compared to Co3O4 (001). The band diagram of the nanoparticles constructed from the various spectroscopic measurements with work function and band gap provides in-depth understanding of the electrocatalytic process.

Essentials of Mo+6/Mo+4 and Ce+4/Ce+3 redox couples in auto-regenerated catalyst for dry methane reforming - Panda, Satyajit; Singh, Gaje; Kaishyop, Jyotishman; Gazi, Md Jahiruddin; Mule, Harshada Mahadev; Khan, Tuhin Suvra; Sharma, Ojasvi; Bordoloi, Ankur (Chemical Engineering Journal, 2025)
Biogas is a potential renewable carbon resource, and dry reforming is one of the promising routes to mitigate via generating syngas, used as a building block for the synthesis of chemicals and fuels. Coke deposition and metal sintering of the reported catalyst systems are the major challenges to developing an economically feasible dry reforming process. Molybdenum oxide is a versatile material with properties like oxygen storage, oxygen mobility, and sulphur tolerance. Here, an oxygen storage capacity enhanced catalyst has been designed by applying a mono layer molybdenum oxide on ceria-magnesia-modified alumina support using a unique chemical vapor deposition method. The Ru and Ni used as active components, and Gd as a promoter were dispersed over the modified support via a precipitation-deposition approach. The most efficient composition is found to be 4 % Ni, 0.5 % Gd, and 0.5 % Ru with Mo-promoted modified alumina with excellent stability up to 500 h for dry reforming reaction studies. Two redox cycles (Mo+6 to Mo+4 & Ce+4 to Ce+3) facilitated a significant number of oxygen vacancies, to limit surface carbon accumulation and support high catalytic stability and activity. The possible reaction pathways and stable surface intermediates were identified by using in-situ DRIFT studies, which included metal carbonyls, carboxylate species, and surface hydroxyl groups. Moreover, the DRIFT studies were supported with CH4-TPSR analysis and DFT studies evidence the formation of CHx species and subsequent oxidation. The additional advantage of the usage of molybdenum is the excellent S-tolerance capacity, which is fully scrutinized experimentally as well as theoretically.
Keywords: and Methane reforming; Coke resistant; Oxygen storage; Redox couple cycles; Sulphur tolerance

Facet dependence for solvent-modulated proton-coupled electron transfer in furfural acetalization on Pd nanostructures - Porwal, Govind; Dandekar, Pallavi; Gorai, Twinkle; Khan, Tuhin Suvra; Haider, M. Ali; Gupta, Shelaka; Vinod, C. P. (Chemical Engineering Journal, 2025)
Furfural dialkyl acetals prepared via acetalization reaction of furfural and alcohols are promising biofuels. Using defined experiments and density functional theory (DFT) simulations, the structure-dependent activity and selectivity for furfural acetalization reaction in the presence of alcohols (methanol, ethanol, propanol and butanol) as solvents was studied over well-defined supported Pd nanostructures (octahedra (111), cubes (100) and spheres (both (111) and (100)). Pd cubes supported over TiO2 in the presence of ethanol as a solvent (at 303 K and balloon pressure H-2) exhibited 78 % conversion and 100 % selectivity for furfural diethyl acetal product in a short time (similar to 180 min). In contrast, Pd octahedra (111) and Pd spheres showed low conversions (18 % and 6 %) at the same reaction conditions. Interestingly, when used as a solvent, methanol showed the highest conversion (90 %) and selectivity (100 %) for furfural acetalization over Pd cubes. DFT simulations provided mechanistic insight into the reactivity of the two different Pd facets (111) and (100) in the presence of alcohol molecules towards furfural acetalization reaction. A three-step reaction mechanism was proposed for furfural acetalization with alcohols: (i) alcohol hydroxyl-dehydrogenation (ii) hydrogenation of furfural carbonyl oxygen, and (iii) formation of hemiacetal product. For all three steps, Pd (100) exhibited low activation barriers (51.6, 26.7 and 76.2 kJ/mol) compared to Pd (111) surface (78.6, 35.8 and 92.2 kJ/mol) in the presence of ethanol. The activation barriers for the above steps were further reduced to 47.8, 23.9 and 64.6 kJ/mol on Pd (100) in the presence of methanol, explaining the experimental high reactivity aided by methanol. DFT calculations elucidated the role of the hydrogen bonding network between the solvent molecules and adsorbate, enabling proton-coupled electron transfer for accelerated reactions.
Keywords: Acetalization; DFT; facet-dependent reactivity; furfural; Furfural dialkyl acetals; solvent effect